PELAKSANAAN UPAYA PAKSA PENGEMBALIAN UANG PENGGANTI DALAM TINDAK PIDANA KORUPSI OLEH KEJAKSAAN TINGGI RIAU - Muhammad Faisal Pakpahan; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
In Article 18 paragraph 1 letter (b) of Law No. 31 of 1999 jo Law No. 20 of 2001 provides for the payment of compensation where the convicts were found guilty in corruption case be obliged to pay compensation numbering as many same with the wealth he gained from corruption. The prosecution as executor is entitled to collect compensation from the convict predetermined guilty in the trial process, but in practice there are many arrears compensation not yet paid by the convict to the prosecution, is where it takes the role of the prosecutor to address arrears compensation that may be detrimental state finances. The problems discussed in this thesis is, First, how the implementation efforts to recover compensation in corruption by the state prosecutor in Riau? Second, is the cause of arrears in cash instead of corruption by the state prosecutor in Riau? Third, How an attempt to avoid the emergence of arrears for compensation in corruption by the state prosecutor in Riau?The method of research in this study, using this type of research is sociological / empirical research sites jurisdiction of the High Court of Riau. In this research, data collection by interview, and literature study. After the data collected then analyzed qualitatively, then conclude with the deductive method is to analyze the problems of the general form into special shapes.From the results of this study concluded, the first implementation of forceful measures refund substitute in corruption by the state prosecutor in Riau has been carried out in accordance with the law of criminal procedure in force, the second cause of arrears compensation in corruption by the state prosecutor Riau them are convicted person is free to choose between pay compensation or choose to corporal punishment or in addition to principal punishments, convicted in the status of the search list (DPO), and the convict did not have possessions in order to pay the compensation. the third effort is made to avoid arrears compensation in corruption by the state prosecutor Riau them with a direct charge to the sentenced person within a period of one month after the issuance of the court decision by a judge who has obtained permanent legal force, return on assets through criminal and asset recovery through civil lines.Keywords: Forced Effort, Money Substitutes, Corruption, the High Court of Riau